2022
DOI: 10.1186/s12913-022-08405-4
|View full text |Cite
|
Sign up to set email alerts
|

How public and private health insurance coverage mitigates catastrophic health expenditures in Republic of Korea

Abstract: Background The private health insurance (PHI) market in Republic of Korea has instituted indemnity insurance plans that provide partial reimbursements for some medical services or costs that are not covered by the National Health Insurance (NHI). To date, no study has estimated the extent to which PHI coverage lowers the economic burden of households’ access to health care. The current study aims to evaluate the design of Korea’s PHI system in terms of coverage using a catastrophic health expen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
13
0
1

Year Published

2023
2023
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 21 publications
(14 citation statements)
references
References 28 publications
0
13
0
1
Order By: Relevance
“…For example, a study in Ghana found that individuals aged 56 to 65 and without employment were less likely to enroll in health insurance, with nearly half of participants paying for membership out of pocket [21]. Similarly, in Korea, a large number of households subscribed to private health insurance, but very few received reimbursements for medical costs or services [22]. These findings underscore the need for policies and interventions to address disparities in health insurance enrollment and coverage.…”
Section: Discussionmentioning
confidence: 99%
“…For example, a study in Ghana found that individuals aged 56 to 65 and without employment were less likely to enroll in health insurance, with nearly half of participants paying for membership out of pocket [21]. Similarly, in Korea, a large number of households subscribed to private health insurance, but very few received reimbursements for medical costs or services [22]. These findings underscore the need for policies and interventions to address disparities in health insurance enrollment and coverage.…”
Section: Discussionmentioning
confidence: 99%
“…In Korea, the National Health Insurance (NHI) system covers 97% of the population, and the remaining population consists of Medical Aid recipients, as well as temporary or illegal residents. 17 The NHI database includes sociodemographic information, healthcare utilisation and national health examination results. 18 Using the NHI database, we extracted data on female patients with RA who claimed insurance between 2010 and 2020.…”
Section: Methodsmentioning
confidence: 99%
“…However, a drawback of this approach is the lack of comprehensive care. In South Korea, 97% of the population is covered by the national health insurance scheme, and medical aid is provided to ensure medical access for the poor [ 3 ]. Under a fee-for-service reimbursement system, providers are encouraged to increase the volume and intensity of patient care rather than improve health outcomes [ 2 ].…”
Section: Introductionmentioning
confidence: 99%